EFFECT OF HEAT AND LIGHT ON ELECTRICAL PROPERTIES OF SI-CNT JUNCTION - Alfaidhi, Anwar Mustafa; Mustafa, Bassam; Uonis, Mohammad (Malaysian Journal of Science, 2020)
Abstract Plasma sputtering was used to deposit a layer of carbon from graphite with thicknesses (20 , 54, 63 nm) on a p-type silicon wafer substrates to prepare Si-CNT (Silicon – Carbon Nano Tubes ) junction without any catalyst . It is found that the I-V characteristics of the junction were similar to the diode properties, which gave confirmation that the carbon layer or in other words that carbon nanotubes behaved as an n-type semiconductor. The effect of heat and illumination with light on the I-V characteristics is studied . at different temperature (32 , 40 , 50 and 60 o C) , the I-V characteristics shows clear effect and increase of conductivity with increasing of temperature for certain thickness . Also studied the effect of light on the I-V characteristics show an increase in the flowing current , the effect of both heat and illumination with light are more pronounced for low thickness of the CNT layer .